It is an algebraic expression with its plus or minus signs missing
-9x^2 - 15x
Expressed algebraically, 3x times 4 is equal to 12x.
A quadratic. For example, x^2 + 3x - 7xy - 12y - 25 = 0
It is: 7xy/21yz = x/3z when simplified
3x x 4y = 12xy
12xy * 3x = 36x2y
The first example that comes to mind is that since 12xy is a factor of 36xy, you could use 12xy. This would have the GCF that you want. ■
2p = 4y - 12xy - 6x, 3q = 12 - 15y so 2p - 3q = 4y - 12xy - 6x - (12 - 15y) = 4y - 12xy - 6x - 12 + 15y = 19y -12xy - 6x - 12
The GCF is 3x.
3x2 - 2y2 = 9x2 + 4y2 - 12xy (subtract 3x2 and add 2y2 to both sides) 0 = 9x2 -3x2 + 4y2 + 2y2 - 12xy 0 = 6x2 + 6y2 - 12xy (divide by 6 to both sides) 0 = x2 + y2 - 12xy or x2 - 2xy + y2 = 0 (x - y)(x - y) = 0 x - y = 0 x = y